2006
DOI: 10.1063/1.2158130
|View full text |Cite
|
Sign up to set email alerts
|

Binary Ni–Nb bulk metallic glasses

Abstract: We studied the glass forming ability of Ni-Nb binary alloys and found that some of the alloys can be prepared into bulk metallic glasses by a conventional Cu-mold casting. The best glass former within the compositional range studied is off-eutectic Ni 62 Nb 38 alloy, which is markedly different from those predicted by the multicomponent and deep eutectic rules. The glass formation mechanism for binary Ni-Nb alloys was studied from the thermodynamic point of view and a parameter ␥ * was proposed to approach the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
107
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(112 citation statements)
references
References 23 publications
1
107
0
4
Order By: Relevance
“…This compositional complexity makes it extremely difficult for different atoms to rearrange their spatial positions so that they are frozen directly into a disordered glassy structure upon cooling. Recently, binary BMG forming alloys have also been developed in a few alloy families [6][7][8][9][10][11][12][13][14], and their GFA is found to be very sensitive to the minor change of chemical composition [15,16]. These further confuse the criterions of GFA in metallic alloys.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…This compositional complexity makes it extremely difficult for different atoms to rearrange their spatial positions so that they are frozen directly into a disordered glassy structure upon cooling. Recently, binary BMG forming alloys have also been developed in a few alloy families [6][7][8][9][10][11][12][13][14], and their GFA is found to be very sensitive to the minor change of chemical composition [15,16]. These further confuse the criterions of GFA in metallic alloys.…”
Section: Introductionmentioning
confidence: 93%
“…r small /r large Cu-Zr [10][11][12] 0.7039 Cu-Hf [7][8][9] 0.6971 Ni-Nb [13] 0.7525 Ca-Al [14] 0.6082 that q ranges from 0.55 to 0.80. Here, we use a binary colloid system to simulate the situation of binary BMGs with large particle (d = 2.9 m) and smaller particles (d = 2.0 m).…”
Section: Alloy Systemmentioning
confidence: 99%
“…The predicted glass-forming composition range in the Ni-Ti system is 24 -77 at.% Ni, which is in well agreement with the experimental glass-forming composition range (28 -72 at.% Ni) prepared by mechanical alloying. Recently, by combining with a new glass-forming ability parameter, the Miedema's model has been used as a guide to searching for the best glass-forming ability composition in binary alloy systems (Xia et al, 2006a(Xia et al, , 2006b(Xia et al, , 2006c. It is argued that the formation of a metallic glass should involve two aspects (Xia et al, 2006a).…”
Section: The Original Miedema's Model For Binary Alloysmentioning
confidence: 99%
“…[17][18][19][20][21] An interesting phenomenon was found that although these binary systems have the broad composition regions forming MG, the best glass formers are located at some pinpoint compositions. 8,9 The existing rules and criteria fail to explain this phenomenon, resulting in the absence of the guiding principle for developing more MG compositions with high GFA in binary alloy systems.…”
Section: Introductionmentioning
confidence: 99%